2019
DOI: 10.1021/acs.jpcc.8b10298
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Molecular Dynamics Study of Hydroxide Diffusion Mechanisms in Nanoconfined Structural Mimics of Anion Exchange Membranes

Abstract: The development of reliable, cost-effective polymer architectures for use as anion exchange membranes (AEMs) is an important challenge facing emerging electrochemical device technologies. Elucidation of key design principles underlying these electrolytes requires a fundamental understanding of the hydroxide ion transport mechanism in the aqueous region of an AEM. To this end, we have carried out a series of atomistic ab initio molecular dynamics calculations. To mimic the complex AEM nanoconfined environment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(142 citation statements)
references
References 75 publications
9
133
0
Order By: Relevance
“…Dispersion forces were accounted for using the Dispersion-Corrected Atomic Core Pseudopotential (DCACP) scheme [ 61 , 62 ] within the Kohn–Sham formulation of Density Functional Theory using the B-LYP exchange-correlation functional [ 63 , 64 ]. The B-LYP+DCACP has been selected for this study, as it has previously been shown to produce satisfactory results for water-acene interactions [ 65 ], liquid water [ 66 ], and hydronium diffusion in bulk water [ 38 , 39 , 40 , 67 ] A detailed description of the construction of the initial structures and of the computational methodology can be found in the Supplementary Information (SI) and in References [ 52 , 53 , 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Dispersion forces were accounted for using the Dispersion-Corrected Atomic Core Pseudopotential (DCACP) scheme [ 61 , 62 ] within the Kohn–Sham formulation of Density Functional Theory using the B-LYP exchange-correlation functional [ 63 , 64 ]. The B-LYP+DCACP has been selected for this study, as it has previously been shown to produce satisfactory results for water-acene interactions [ 65 ], liquid water [ 66 ], and hydronium diffusion in bulk water [ 38 , 39 , 40 , 67 ] A detailed description of the construction of the initial structures and of the computational methodology can be found in the Supplementary Information (SI) and in References [ 52 , 53 , 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…The CN values found suggest that before a PT occurs between the anion nascent water molecule, the water must have a first solvation shell of one water o and an incomplete second solvation shell. Values of δ > 0.5 are considered to be inactive complexes with respect to PT, while values of δ < 0.1 are considered to be "active" and are associated with PT events [41,42,52,69,70]. In Figure 7b, we present the O next O RDF and CNs for δ < 0.1 and δ > 0.5, where, O next represents the first neighbor oxygen to the SO 3 H oxygen, and O represents water and hydronium oxygens.…”
Section: Hydronium Ion Diffusion In the Pemmentioning
confidence: 99%
See 3 more Smart Citations